Study of Solid Particle Erosion Behaviour of SS 304 at Room Temperature. (2016) - Patel, Mayank; Patel, Darshan; Sekar, S.; Tailor, P.B.; Ramana, P.V.
Abstract: Erosion is one of the major problems in many engineering system including power generation units, steam/jet turbines, chemical processing equipments, and air craft engines. In the present study erosion test were conducted using air-jet erosion test rig on boiler tube steel SS 304. The impact velocity was 40m/s, the impingement angle was 30 o and 90 o on SS 304 at room temperature. Alumina particles of size 50 microns were used as the erodent. The initial and final weight of the specimens were taken using electronic weighing machine having a resolution of 0.01 mg. Erosion rate was determined as the ratio of weight loss of the material to the weight of eroding particles. Scanning electron microscope (SEM), equipped with an energy dispersive X-ray analyser (EDAX) was used to analyse the eroded surfaces. Results indicated that SS 304 showed higher erosion rate at 30 o as compared to 90 o impact angle, indicating ductile mode of erosion.